2013
DOI: 10.1116/1.4812717
|View full text |Cite
|
Sign up to set email alerts
|

Tin oxide atomic layer deposition from tetrakis(dimethylamino)tin and water

Abstract: Due to the abundance and usefulness of tin oxide for applications such as transparent conductors, sensors, and catalysts, it is desirable to establish high quality atomic layer deposition (ALD) of this material. ALD allows for uniform, conformal coating of complex topographies with ultrathin films and can broaden the applicability of tin oxide to systems such as nanostructured solar cells. The present work examines the ALD of tin oxide by means of the precursor tetrakis(dimethylamino)tin and water as a counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 80 publications
10
77
0
1
Order By: Relevance
“…For the pure SnO x films the thickness, and thereby the growth rate, decreases with increasing deposition temperature, from~1.3 Å/cycle at 90°C to~0.6 Å/cycle at 180°C. This decrease in growth rate with increasing deposition temperature correlates well with the findings of [18], which also uses TDMASn and water as precursors, but Si(100) as substrates, and shows that our pure SnO x behaves as expected.…”
Section: Composition and Growth Ratesupporting
confidence: 87%
See 3 more Smart Citations
“…For the pure SnO x films the thickness, and thereby the growth rate, decreases with increasing deposition temperature, from~1.3 Å/cycle at 90°C to~0.6 Å/cycle at 180°C. This decrease in growth rate with increasing deposition temperature correlates well with the findings of [18], which also uses TDMASn and water as precursors, but Si(100) as substrates, and shows that our pure SnO x behaves as expected.…”
Section: Composition and Growth Ratesupporting
confidence: 87%
“…Similar changes of the band gap as in Fig. 1(d) are also attributed to quantum confinement effects for X-ray amorphous SnO x [18] and for Zn 2 SnO 4 nanoparticles [11,26]. Furthermore, it is shown that films consisting of wurtzite isotropic shaped ZnO nanoparticles in size range up to 9 nm are small enough to display quantum confinement effects as well, and that the band gap, E g (in eV), decreases with increasing particle diameter, d (in nm), according to the expression E g = 3.30 + 0.293 / d + 3.94 / d 2 [25,27].…”
Section: Optical Propertiessupporting
confidence: 67%
See 2 more Smart Citations
“…36 This may seem in contradiction to the observation of incomplete removal of the -N(CH 3 ) 2 (dimethylamino, DMA) ligands. However, we propose the following explanation: Density functional theory (DFT)…”
Section: B Incomplete Elimination Of Precursor Ligands During Ald Ofmentioning
confidence: 85%